The Psychological Characteristics of People with High and Low Levels of Professional Well-Being - Ingrida Baranauskienė; Alla Kovalenko; Borys Pakhol (Social Welfare: Interdisciplinary Approach, 2024)
The article presents a comparative analysis of the psychological characteristics of people having high and low levels of professional well-being. There were significant differences for all studied indicators between groups with high and low professional well-being. The widest differences between the two groups were found for average values of professional commitment, job satisfaction, autonomous motivation, in-demand profession, and professional psychological well-being; the smallest differences were determined for average values of life satisfaction, climate in a team and controlled motivation.